Study on the Selective Behavior of Brachymystax tsinlingensis Li, 1966 (Order: Saloniformes, Family: Salmonidae) on Substrate Color and Type - Lin Zhang; Rongqun Song; Jian Shao (Animals)
Substrate is an important component of a fish’s habitat environment. Fish preferences for substrate influence their growth and development, feeding, hiding, schooling, and reproduction. To explore the habitat preference of Brachymystax tsinlingensis, this study was conducted on the preferences of B. pre-smolts, post-smolts, and juveniles for three substrate colors, white, blue, and black, and four substrate types, sand (<0.5 cm in diameter), small gravel (1–2 cm in diameter), medium gravel (5–7 cm in diameter), and large gravel (12–16 cm in diameter), which were investigated in light (10–60 lx) and dark (no light) environments. The results showed that the individual populations of B. tsinlingensis in three periods of time had a clear preference for substrate color, preferring black substrate and staying away from blue substrate under both light and dark environmental conditions; B. tsinlingensis pre-smolts and post-smolts preferred sandy substrate, and juveniles preferred medium gravel substrate. The choice of substrate color and substrate type by B. tsinlingensis is a manifestation of the living environment characteristics of this species, which is conducive to their hiding, better avoidance of enemies, and improvement of their survival rate. Based on the research results and the early biological characteristics of B. tsinlingensis, it is recommended to use black or dark substrate during the cultivation of B. tsinlingensis fry. During the larval fish stage, a sandy substrate environment should be provided. During the juvenile fish stage, a medium-gravel environment should be provided.